Transcriptomic characterization of classical monocytes highlights the involvement of immuno-inflammation in bone erosion in Rheumatoid Arthritis - Sales, Lucas Peixoto; Hounkpe, Bidossessi Wilfried; Perez, Mariana Ortega; Caparbo, Valéria Falco; Domiciano, Diogo Souza; Borba, Eduardo Ferreira; Schett, Georg; Figueiredo, Camille Pinto; Pereira, Rosa Maria Rodrigues (Frontiers in Immunology, 2023)
Evidence-based data suggest that under inflammatory conditions, classical monocytes are the main source of osteoclasts and might be involved in bone erosion pathophysiology. Here, we analyze the transcriptomic profile of classical monocytes in erosive and non-erosive rheumatoid arthritis patients in order to better understand their contribution to bone erosion.Methods: Thirty-nine premenopausal RA patients were consecutively enrolled and divided into two groups based on the presence of bone erosions on hand joints. Classical monocytes were isolated from peripheral blood through negative selection, and RNA-seq was performed using a poly-A enrichment kit and Illumina® platform. Classical monocytes transcriptome from healthy age-matched women were also included to identify differentially expressed genes (DEGs). Therefore, gene sets analysis was performed to identify the enriched biological pathways.Results: RNA-seq analysis resulted in the identification of 1,140 DEGs of which 89 were up-regulated and 1,051 down-regulated in RA patients with bone erosion compared to those without bone erosions. Among up-regulated genes, there was a highlighted expression of IL18RAP and KLF14 related to the production of pro-inflammatory cytokines, innate and adaptive immune response. Genes related to collagen metabolism (LARP6) and bone formation process (PAPPA) were down-regulated in RA patients with erosions. Enriched pathways in patients with erosions were associated with greater activation of immune activation, and inflammation. Interestingly, pathways associated with osteoblast differentiation and regulation of Wnt signaling were less activated in RA patients with erosions.Conclusions: These findings suggest that alterations in expression of monocyte genes related to the inflammatory process and impairment of bone formation might have an important role in the pathophysiology of bone erosions in RA patients.